Scientific Approach With Inquiry Method To Improve Students' Science Literacy In Natural Changes - debby enjelika putri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2026)
The low level of elementary school students' scientific literacy requires innovative and student-centered learning methods. This study aims to determine the effectiveness of the scientific approach using the inquiry method in improving the scientific literacy of fifth-grade elementary school students regarding the topic of natural changes. This research employed a quantitative method with a pre-experimental design, specifically the One-Group Pretest-Posttest Design. The sample consisted of 26 students selected using a saturated sampling technique. Data collection methods included tests, observations, and documentation. The research instrument was an essay test developed based on the PISA 2022 scientific literacy indicators. Data analysis was conducted using the N-Gain formula to determine the level of improvement in students’ scientific literacy. The results showed a significant increase in students’ scientific literacy skills, with an average N-Gain score of 0.64, falling into the medium category. These findings indicate that the scientific approach combined with the inquiry method is highly effective in improving students’ scientific literacy regarding natural change.